Akibat Hukum Pendaftaran Penyelesaian Sengketa Alternatif - Dewa Nyoman Rai Asmara Putra; I Putu Rasmadi Arsha Putra (Departemen Hukum Perdata, 2020)
Everyone is allowed to be in conﬂict with legal issues that exist in civil procedural law called cases that contain both disputes and those that do not contain disputes. Disputes are indeed important to mature the way of thinking, but more importantly must be agreed. Managing disputes means ﬁ nding the best way to resolve them. The best way to resolve disputes is by means of a win-win solution in Act No. 30 of 1999 concerning Alternative Dispute Resolution (ADR). Settlement of disputes with ADR has the highest degree because it is really ﬁ nished, not resolved the dispute, as long as each party obeys all the results of the agreement that has been made. In Article 6 paragraph (7) of Act No. 30 of 1999 concerning Alternative Dispute Resolution (ADR), the results of the agreement must be made in written form and must be registered with the District Court. This research focuses on studying the method of registration proposed in article 6 paragraph (7). Law No. 30 of 1999. The results of this study found facts regarding the payment of the results of the agreement to the District Court does not have any legal requirements for the parties related to legal certainty, justice and beneﬁ ts for the agreement.